Os jovens em círculos de leitura literária : uma proposta para espaços alternativos - Gonçalves, Luciana Sacramento Moreno (2014)
In this thesis, we talk about the encouragement to literary experience, through Reading Circles (YUNES, 1999; COSSON, 2006), among young people, in non-formal social educational spaces. The research is situated at the Centro de Referência e Assistência Social, in sections of a city of the Metropolitan Region of Salvador. Our goal is to identify which effects such practice causes in the readers. A study on the relationship about Literature and Society takes part in the theoretical foundation, for us to think about this artistic demonstration as a right given to all human beings and to analyze the Literature as one of the resources to humanize the man (CANDIDO, 2000). We present a reflection about the specialties and the importance of the literary text (AGUIAR, 2006; ZILBERMAN, 2002) to discuss about the literary experience as a door of entrance for reader s formation (LARROSA, 1996; YUNES, 1999).We are for the mediation as an essential process for promoting effective and successful actions. We understand reading as a cultural practice which is to be learned, taught and history-told (BORDIEU, 1996; CHARTIER, 1998). The methodology way followed by this research has got a qualitative, descriptive and interventionist character, because of that, we re based on the Action-Research. In order to obtain the data we decided by the use of an exploratory research diary, besides the questionnaires applied during the Circles and semi-structured interviews, individual or in small groups. At the end of the research, we observed that among young people, changes referring to their conception on reading and Literature. They start to bring experiences from their lives to give sense to the text, they start to think as a group, to speak safely and spontaneously and, as a consequence, to evaluate critically important topics such as family matters, young, genre, ethnic and sexual identity. They try to socialize their literary experiences, developed in the Circles, among neighbors, relatives and friends. Because of that, we state that the young people, when entering the practice of reading, declare not to like reading and Literature, and after instrumented and close to them in a gradual, dynamic and free way, change their position. We know that Literature by itself doesn t change the current social realities; however we state that it may raise awareness of the readers through a self-knowledge process, making them implement group transforming actions.